Meningkatkan kesehatan mental dengan membangun hubungan kelekatan antara orang tua dan anak - Dewi Anggraini; Amalia Juniarly; Sayang Ajeng Mardhiyah; Maya Puspasari (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Improves Mental Health by Develop Attachment between Parents and Children. Mental health is an optimal and harmonious condition of physical, intellectual and emotional development and takes into account all aspects of human life. Therefore, a mentally healthy child is a child who is able to deal with problems in his life. The parenting style greatly affect aspects of child growth and development especially the attachment relationship between parents and children. This output point activity aims to improve mental health of their children by building close relationships between parents and children. This event was carried out in Sementul Village, Rantaubayur District, Musi Banyuasin, South Sumatra. The participant of this event are students from preschool, primary school and junior high school with their mother. The results of the observations during the activity showed the community needs education about attachment between parents and children, so it takes efforts from various professional such as educational psychologist and development psychologist.